At the Threshold of the Visible : Minuscule and Small-Scale Art, 1964-1996 - Lang, Sandra; Rugoff, Ralph; Stewart, Susan; Herbert F. Johnson Museum of Art - Cornell University Ithaca (NY); Maryland Institute of Art, Baltimore; Art Gallery of Ontario, Toronto; Art Gallery of Windsor; Virginia Beach Center for the Arts, Virginia Beach; Santa Monica Museum of Art, Santa Monica; Edmonton Art Gallery, Edmonton (New York : ICI (Independent Curators International), 1997)
Burden, Chris ; Byars, James Lee ; Davis, Gene ; Diamond, Jessica ; Fiskin, Judy ; Friedman, Tom ; Huws, Bethan ; Kabakov, Ilya ; Keister, Steve ; LeDray, Charles ; LeMoine, Elizabeth ; Liddell, Siobhan ; Limone, Guy ; Miller, John ; Nelson, Joan ; Ono, Yoko ; Rosenberg, Aura ; Ross, Michael ; Samore, Sam ; Sandaldjian, Hagop ; Santino, Peter ; Shapiro, Joel ; Sugimoto Hiroshi ; Tuttle, Richard ; Vallance, Jeffrey ; Wilke, Hannah ; Wurtz, B.
biog. + Checklist of the exhibition p. 86-93
Engels
At the Threshold of the Visible, Herbert F. Johnson Museum of Art - Cornell University Ithaca (NY), August 30 - October 26, 1997 ; Maryland Institute of Art Baltimore, November 21 - December 21, 1997 ; Art Gallery of Ontario, Toronto, January 28 - April 22, 1998 ; Art Gallery of Windsor, Windsor, May 2 - June 28, 1998 ; Virginia Beach Center for the Arts, Virginia Beach, June 26 - August 23, 1998 ; Santa Monica Museum of Art, Santa Monica, October 17 - December 12, 1998 ; Edmonton Art Gallery Edmonton, April 10 - June 13, 1999
boek